Differentiated Instruction in Biology Learning: Meta-Analysis - Sembiring, Dian Arisandy Eka Putra; Yusuf, Muhammad; Sadikin, Ali; Mursyd, Danial; Hendra, Robi (BIODIK, 2024)
In the context of the ’Merdeka’ curriculum and educational diversification, differentiated instruction emerges as a pivotal strategy for addressing diverse learning needs within biology education. Through a comprehensive meta-analysis, this study categorizes existing research, assesses the application across educational levels, and evaluates the impact of differentiated instruction, particularly highlighting its effectiveness in higher education facilitated by e-PJBl and learning media. The research predominantly uncovers the use of Classroom Action Research, with a notable effect size in applications at the higher education level, suggesting a marked improvement in learning outcomes. These findings call for an expanded implementation of differentiated instruction to better cater to student needs, ultimately aiming to enhance the quality of biology education across all levels. Key words: Differentiated Instruction, Biology Learning, Meta-Analysis, Merdeka Curriculum Abstrak Dalam konteks kurikulum ’Merdeka’ dan diversifikasi pendidikan, instruksi diferensiasi muncul sebagai strategi pivotal untuk menangani kebutuhan belajar yang beragam dalam pendidikan biologi. Melalui meta-analisis yang komprehensif, studi ini mengkategorikan penelitian yang ada, menilai aplikasi di seluruh tingkat pendidikan, dan mengevaluasi dampak instruksi diferensiasi, khususnya menyoroti efektivitasnya dalam pendidikan tinggi yang difasilitasi oleh e-PJBL dan media pembelajaran. Penelitian ini terutama mengungkapkan penggunaan Classroom Action Research, dengan ukuran efek yang luar biasa dalam aplikasi di tingkat pendidikan tinggi, yang menunjukkan peningkatan yang signifikan dalam hasil belajar. Temuan ini menuntut implementasi yang diperluas dari instruksi yang beragam untuk lebih baik memenuhi kebutuhan siswa, pada akhirnya bertujuan untuk meningkatkan kualitas pendidikan biologi di semua level. Kata kunci: Pembelajaran berdiferensiasi, Pembelajaran biologi, meta-analisis, kurikulum merdeka